(untitled) (American Journal of Economics and Business Innovation, 2025)
Community businesses aim to grow the entrepreneurial spirit of the community in general and, in particular, to foster the entrepreneurial spirit of its members, so community businesses need to be maintained and developed. This study aims to determine the effect of increasing competitiveness and market expansion on community business. This research was designed quantitatively with the research sample being members of the above hand community business. The research data collection techniques consisted of observation, questionnaires, and documentation. This research data analysis uses multiple linear regression. The results of this study indicate that simultaneously increasing competitiveness and market expansion has a significant effect on community business, while partially the two variables have no effect. It shows that increasing competitiveness and market expansion must be implemented together to improve community business because these two things cannot be done separately as the results of this study.